PENGEMBANGAN KANVAS MODEL BISNIS SOSIAL DEMI OPTIMALISASI KINERJA USAHA BERBASIS SOSIAL - Suwarna Putri, Patrisia Anggita; Pranatasari, Fransisca Desiana (Ma Chung Press, 2024)
The role of MSMEs for Indonesia is very large for economic growth. In fact, the number can reach 99% of all business units in Indonesia. Because of this important role, MSMEs need special attention in their sustainability. Agradaya is one of the social and community-based MSMEs that carries out business development based on the triple bottom line, namely People, Planet, Profit. creating a more sustainable business and environment through partnerships with small farmers and sustainable agricultural practices. Agradaya has products that focus on health benefits with natural ingredients produced from selected local plants without artificial ingredients. This study aims to understand the description of the business model in social business. The research method was carried out with a qualitative approach, with interview techniques, observation and documentation as data collection techniques. Triangulation techniques were used as data validity. The analysis tool used was the Social Business Model Canvas. The Social Business Model Canvas is a concept of the Business Model Canvas from Osterwalder but adds two important blocks that represent the mission and impact as a form of innovation in social-based business models. This tool is suitable for use because it can provide a link between social impact and economic impact so that later it can recommend the right strategy for the company. Thus, it can increase competitiveness for social-based companies and various social practices of companies in Indonesia. Social Business Canvas Social Business Model is appropriately applied to social-based businesses so that it can map the business effectively.